We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
138
1
avatar+112 

ax-b=c, for x

 

 

a=h(a+b)/2, for h

 Feb 27, 2019
 #1
avatar+103122 
+2

ax-b = c, for x

 

Add b to both sides

x = b + c         

 

Divide both sides by a

 

x = ( b + c) /   a

 

 

a=h(a+b)/2, for h

 

Multiply both sides by 2

 

2a = h (a + b)       

 

Divide both sides by (a + b)

 

2a / ( a + b)  = h

 

 

cool cool cool

 Feb 27, 2019

7 Online Users